COVID-19-Associated Multisystem Inflammatory Syndrome Complicated with Giant Coronary Artery Aneurysm - Mohammad Reza Navaeifar; Leila Shahbaznejad; Ali Sadeghi Lotfabadi; Mohammad Sadegh Rezai (Case Reports in Pediatrics)
In the early stages of the outbreak of the novel coronavirus disease 2019 (COVID-19), it was assumed that this infection is very mild and uncommon in children. However, recent reports have shown that children may also develop the disease and its severe complications. These complications included shock, multisystem inflammatory syndrome in children (MIS-C), and pneumonia in children. A previously healthy 14-month-old boy presented with fever, irritability, and skin rash, besides changes in the lips, conjunctiva, and tongue. His medical history, clinical presentations, treatment, laboratory data, and follow-up information were recorded. He was treated according to the diagnosis of Kawasaki disease (KD). He had a history of close contact with a COVID-19 patient. However, the result of reverse transcription-polymerase chain reaction (RT-PCR) assay for COVID-19 was negative. Immunoglobulin M for COVID-19 was positive (1.20), while immunoglobulin G was negative (0.37). Three weeks later, seroconversion of COVID-19 immunoglobulin G (1.42) occurred. Despite treatment with two doses of intravenous immunoglobulin and methylprednisolone, coronary artery ectasia was detected. On the sixth day of hospitalization, the patient experienced hypotension, which necessitated treatment with inotropic drugs and resulted in a change of diagnosis to MIS-C. The later echocardiography showed evidence of coronary artery aneurysm (CAA), which finally changed to giant CAA. Although the patient was treated with infliximab, the size of CAA showed a significant decrease in the one-month follow-up. This is the first report of MIS-C during the COVID-19 pandemic in Iran, accompanied by KD, which was complicated with giant CAA.